Staphylococcus aureus Pneumonia in the Community - He, Hangyong; Wunderink, Richard G. (Seminars in Respiratory and Critical Care Medicine, 2020)
Staphylococcus aureus is an emergent etiology of community-acquired pneumonia (CAP) over the past 2 decades, with severe community-acquired pneumonia (SCAP) caused by methicillin-resistant S. aureus (MRSA) leading to critical illness and death. S. aureus colonization is associated with a high incidence of pneumonia. Panton-Valentine leukocidin (PVL) is one of the most important virulence factors of S. aureus associated with serious complications. In recent years, community-associated MRSA (CA-MRSA) clones that caused infections in young adults and healthy individuals with no exposure to health care settings and no classical risk factors have emerged. Clinical features at admission including concurrent influenza infection, hemoptysis, multilobar infiltrates, and neutropenia should suggest S. aureus CAP. Sputum Gram stains, cultures (or tracheobronchial aspirates or bronchoalveolar lavage in mechanically ventilated patients), polymerase chain reaction (nasopharyngeal or oropharyngeal or lower respiratory tract specimens), and two sets of blood cultures should be obtained from patients presenting with severe S. aureus CAP. For CAP due to methicillin-susceptible S. aureus, first-line therapy is usually cefazolin, oxacillin, or ceftaroline. For CA-MRSA pneumonia, linezolid is recommended. If vancomycin or teicoplanin are used, combination with clindamycin or rifampicin should be considered in cases of PVL-positive MRSA CAP.
Keywords: Staphylococcus aureus; community-acquired pneumonia; methicillin-resistant S. aureus; Panton-Valentine leukocidin